HUBUNGAN KEJADIAN DEMAM BERDARAH DENGUE DENGAN IKLIM DI KOTA PRABUMULIH TAHUN 2014-2017 - Ritawati Ritawati; Yanelza Supranelfy (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
Background : Dengue hemorrhagic fever (DHF) is a vector-based disease which is the main cause of death in tropical countries. Climate change affects the increasing incidence of dengue fever from vector borne disease. The climate variation (temperature, humidity, average air pressure, wind speed, sun illumination, rainfall and rainy day) in Prabumulih City from 2014-2017. Method : The data collected is secondary data in the form of climate factor and the number of dengue cases. Result: Statistical tests show that there is a significant relationship between temperature (p value 0.029) and average air pressure (p value 0.013) with the incidence of DHF. Conslusion : this study indicate that there is a significant relationship between temperature and average air pressure with the incidence of DHF. Air humidity, wind speed, prolonged sun illumination, rainfall and the number of rainy days are insignificant with the incidence of DHF.